UPAYA MENINGKATKAN HASIL BELAJAR PASSING KAKI BAGIAN DALAM PADA PERMAINAN SEPAK BOLA MELALUI WALL BALL SISWA KELAS V-A SDN TAKTAKAN 1 - Subagio, Rohmad; Dzil Ikrom, Fadhli; Rahmat, Mamat (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to test hypotheses and provide empirical evidence regarding the role of efforts to improve learning outcomes of inside foot passing in soccer through Wall Ball for Grade V-A students of SDN Taktakan 1. This research employs an experimental method with a